Simple Design of Double-Layer Antireflection Coating for Er-Doped Glass Laser Application - Mai, Van Huy; Duong, Chi Dung; Le, Hoang Hai; Tran, Linh Khuong; Jaffré, Alexandre; Blanc, Emmanuel; Schneegans, Olivier (Communications in Physics, 2022)
In an Erbium-doped glass laser resonator, parasitic light oscillations (yielding a lowering of the output laser beam power) may be avoided by deposition of well-adapted antireflection coatings on the edges of the active glass medium. However, towards laser application, efficient double-layers are scarce in literature. Here, we propose a simple design of double-layer (total thickness < 490nm) composed of thin films of MgF2 and Al2O3, materials that are easy to deposit by electron beam evaporation. Such coating design allows a calculated reflectance to be lower than 0.01% in the considered 1530-1570nm Near-Infrared range.